Acceptance and perceptions of generic substitution among pharmacists: A preliminary study in Vietnam - Quang Vinh Tran; Thoai Dang Nguyen; Tram Thi Huyen Nguyen; Nhi Hoang Yen Ngo; Trung Quang Vo (GarVal Editorial Ltda., 2018)
Context: Over the last ten years, many research studies concerning pharmacists' perceptions of generic medicines have been conducted worldwide, although this issue remains underexplored in Vietnam. Aims: To evaluate pharmacists' views on generic medicines and to investigate the generic substitution practices in community pharmacies in the context of Vietnam. Methods: A cross-sectional survey comprising a 24-item self-administered anonymous questionnaire was distributed to 480 pharmacists in eleven provinces in southern Vietnam between December 2016 and March 2017. The main outcome measures were pharmacists' views on generic medicines. Results: Of the 480 pharmacists who received the questionnaire, the effective response rate was 35.63% (n=171 pharmacists); however, 45 pharmacists chose all three correct generic names. Some 47.3% of respondents indicated that all the products that are approved as exhibiting generic equivalence can be considered therapeutically equivalent to the innovator drugs. Yet, 25.2% of respondents agreed that generic medicines are of inferior quality to branded medicines. The pharmacists who graduated from universities and those who had undergone only a short period of training differed significantly in terms of their knowledge and perceptions. About 60.2% of pharmacists recommended generics over branded products. Approximately 89% of respondents disagreed with the notion of implementing certain compulsory generic substitutions in Vietnam. Conclusions: The pharmacists who had completed only a short training period exhibited a lack of knowledge regarding generic names. This issue should hence be addressed by both pharmacy educators and relevant government agencies in order to ensure the wider use of generic products.